86.1k views
4 votes
Solve the equation.
9x^3 - 36x = 0

Solve the equation. 9x^3 - 36x = 0-example-1
User Dasdachs
by
5.3k points

1 Answer

6 votes

Answer:

x = -2,0,2

Explanation:

9x^3 - 36x = 0

Factor out 9x

9x(x^2 -4) =0

Factor inside the parentheses, which is the difference of squares

(a^2 -b^2 = (a-b)(a+b)

9x (x-2)(x+2) = 0

Using the zero product property

9x =0 x-2=0 x+2 =0

x=0 x=2 x=-2

x = -2,0,2

User Alexy
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.